1997
DOI: 10.1002/(sici)1096-9861(19970602)382:2<247::aid-cne8>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of neuronal apoptosis inhibitory protein-like immunoreactivity in the rat central nervous system

Abstract: We have recently shown that spinal muscular atrophy (SMA), an autosomal recessive disorder characterized by motor neuron loss, is associated with deletion of a gene that encodes the neuronal apoptosis inhibitory protein (NAIP). In the present study, we have examined the distribution of NAIP-like immunoreactivity (NAIP-LI) in the rat central nervous system (CNS) by using an affinity-purified polyclonal antibody against NAIP. In the forebrain, immunoreactive neurons were detected in the cortex, the hippocampus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
12
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…This autosomal recessive condition is caused by Roy et al, 1995;Chen et al, 1998;mNAIP1-6, mouse NAIP-1 through 6 (AF007769) Yaraghi et al, 1998; NAIP-rs 1 through 6, NAIP related sequence 1 (U66324), 2 (U66325), 3 (U66326), 4 (U66327), 5 (U66328), 6 (U66329) Scharf et al, 1996; rNAIP, Rat NAIP (partial cDNA) Korneluk et al, (unpublished); HIAP1, human IAP1 (U45878) Liston et al, 1996; cIAP2, cellular IAP2 (L49432) Rothe et al, 1995; MIHC, mammalian IAP homolog C (U37546) Uren et al, 1996; hITA, human inhibitor of T-cell apoptosis, Nicholl et al, 1996; MIAP1, mouse IAP1 (U88908) Liston et al, 1997;RIAP1, rat IAP1 Holcik et al, (unpublished); PIAP, porcine IAP (U79142) Stehlik et al, 1998b; ITA, inhibitor of T-cell apoptosis (U27466) Digby et al, 1996;ch-IAP1, chicken a severe loss of motor neurons which results in fatal accid paralysis (Dubowitz, 1995). While the contiguous SMN gene has been found to be causative of SMA , the tissue expression of NAIP (Xu et al, 1997a) combined with its strong in vitro (Liston et al, 1996) and in vivo (Xu et al, 1997b) neuroprotective eect make it a likely candidate for modi®cation of the SMA phenotype. It is postulated that motor neurons missing NAIP withstand the low cellular levels of SMN protein poorly and dying earlier than they would have otherwise resulting in more severe disease (MacKenzie, 1998).…”
Section: Non-viral Iapssupporting
confidence: 63%
“…This autosomal recessive condition is caused by Roy et al, 1995;Chen et al, 1998;mNAIP1-6, mouse NAIP-1 through 6 (AF007769) Yaraghi et al, 1998; NAIP-rs 1 through 6, NAIP related sequence 1 (U66324), 2 (U66325), 3 (U66326), 4 (U66327), 5 (U66328), 6 (U66329) Scharf et al, 1996; rNAIP, Rat NAIP (partial cDNA) Korneluk et al, (unpublished); HIAP1, human IAP1 (U45878) Liston et al, 1996; cIAP2, cellular IAP2 (L49432) Rothe et al, 1995; MIHC, mammalian IAP homolog C (U37546) Uren et al, 1996; hITA, human inhibitor of T-cell apoptosis, Nicholl et al, 1996; MIAP1, mouse IAP1 (U88908) Liston et al, 1997;RIAP1, rat IAP1 Holcik et al, (unpublished); PIAP, porcine IAP (U79142) Stehlik et al, 1998b; ITA, inhibitor of T-cell apoptosis (U27466) Digby et al, 1996;ch-IAP1, chicken a severe loss of motor neurons which results in fatal accid paralysis (Dubowitz, 1995). While the contiguous SMN gene has been found to be causative of SMA , the tissue expression of NAIP (Xu et al, 1997a) combined with its strong in vitro (Liston et al, 1996) and in vivo (Xu et al, 1997b) neuroprotective eect make it a likely candidate for modi®cation of the SMA phenotype. It is postulated that motor neurons missing NAIP withstand the low cellular levels of SMN protein poorly and dying earlier than they would have otherwise resulting in more severe disease (MacKenzie, 1998).…”
Section: Non-viral Iapssupporting
confidence: 63%
“…The first discovered mammalian IAP, neuronal apoptosis inhibitory protein (NAIP), or baculoviral IAP repeat-containing protein 1 (BIRC1), was cloned as a candidate gene for the childhood disorder spinal muscular atrophy (SMA) (Roy et al 1995). The expression of NAIP has thus been studied extensively in the central nervous system (CNS) (Xu et al 1997b;Pari et al 2000) and during development (IngramCrooks et al 2002). The distribution of NAIP-like immunoreactivity was examined in the rat CNS by using an affinity-purified polyclonal antibody (E1.0) against human NAIP (Xu et al 1997b).…”
mentioning
confidence: 70%
“…The expression of NAIP has thus been studied extensively in the central nervous system (CNS) (Xu et al 1997b;Pari et al 2000) and during development (IngramCrooks et al 2002). The distribution of NAIP-like immunoreactivity was examined in the rat CNS by using an affinity-purified polyclonal antibody (E1.0) against human NAIP (Xu et al 1997b). This investigation demonstrated a wide distribution of NAIP-like species in the rat CNS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that the neuronal apoptosis inhibitory protein (NAIP) is deleted in a significant proportion of SMA patients (2). Full-length functional NAIP is absent in most individuals with type I SMA, and there exists a close correlation between the regional distribution of NAIP in the CNS and the neurodegenerative alterations in SMA (3). These observations are consistent with the neurodegenerative character of SMA.…”
mentioning
confidence: 99%